Characteristics of the Oil Water Contact Zone of Nhar Umr and Mishrif Reservoirs in Kumait and Dujaila Oil Fields, Southern Iraq, Using Vp/Vs Ratio and Porosity Logs Data - Nassir, Nowfal A.; Al-Banna, Ahmed S.; Al-Sharaa, Ghazi H. (Iraqi Journal of Science, 2020)
The detailed data of the Vp/Vs ratio and porosity logs were used to detect the Oil-Water Contact Zone (OWCZ) of Nahr Umr sandstone and Mishrif limestone reservoir formations in Kumiat (Kt) and Dujaila (Du) oil fields, southeastern Iraq. The results of OWC were confirmed using P-wave, Resistivity, and Water Saturation (Sw) logs of Kt-1 and Du-1 wells. It was found that the values of the oil-water contact zone thickness in Nahr Umr sandstone and Mishrif limestone were approximately one meter and eight meters, respectively. These results suggest that the OWCZ is possibly thicker in the carbonate rock than clastic rock formations. The thickness of OWCZ in the clastic rocks changed from one part to another, depending on several factors including mineral composition, grain size, porosity, pore shape, and fluid type.